Externalities of public spending for education in economic growth - Barrientos, Carmen (2020)
When economic growth is considered as a measure of the welfare of the population, it constitutes one of the basic objectives of economic policy; Therefore, the study of the factors or causes that originate it has been, and continues to be, one of the relevant topics in the economic discussion. The foregoing gave rise to the interest of determining whether public spending for education generated a positive or negative externality in the economic growth of the countries of the Andean region in the period 2000-2015. The study was conducted under the quantitative approach, specifically through the development of an econometric model. The main results show that in the study period, the countries of the Andean region developed under similar contexts and policies, where the characteristics and decisions of each country regarding public spending, although they differentiated them, in turn allowed to identify a joint reaction at the level of the region, regarding the results of social policies, concluding that public spending for education came to generate positive externalities in the economic growth of the Andean region.